The handbook of strategic public relations and integrated communications - Caywood, Clarke L., 1947- (New York : McGraw-Hill, 2012)
The second edition of this resource includes 70 leading authors in the field of public relations and communications, 27 new chapters and 44 new authors addressing the major changes in the field. Each chapter has a QR code that links to the contributors' biography, chapter introduction, more images, mobil and full websites for the book.
Introduction to public relations and integrated marketing communications. Twenty-first century public relations : the strategic stages of integrated marketing communications / Clarke L. Caywood -- Communications research : foundational methods / Anders Gronstedt and Clarke L. Caywood-- Communications research: Dynamic digital methods / Clarke L. Caywood -- Public relations law / Karla K. Gower -- A brief history of public relations: The unseen power / Scott M. Cutlip and Brent Baker -- Ethics: Grounding the promotional strategies of China's tobacco industry in ethics / Cornelius Pratt -- Stakeholder leadership in public relations: The stakeholder concept: empowering public relations / Clarke L. Caywood -- The key stakeholders : your employees / Keith Burton -- Consumer insight in a digital age / Geraldine Henderson -- Marketing public relations : cementing the brand / Patricia T. Whalen -- Investor relations for shareholder value : communicating with the market / Nancy Hobor -- Mergers and acquisitions : Communications between the lines / Joele Frank -- Charities and corporate philanthropy : Giving back / John A Koten -- Government public information: Portal to the public / Brent Baker -- Broadcast media as broadcast public relations / Tim Larson and Craig Wirth -- Digital communities: Social media in action / Richard Edelman, Robert Holdheim, Mark Hass, Phil Gomes, Steve Rubel, Dereck Creevey -- Global media relations: traditional through 2.0 / Matthew P. Gonring -- Nongovernmental organizations : solving society's problems / Ray Boyer, Scott McCallum -- Associations : a strong voice / Richard P. Hanneman -- Agencies : Managing a global communications firm / Ray Kotcher -- Issues management methods for reputational management / James E. Arnold, Raymond P. Ewing -- State and local government relations: guiding principles / L. James Nelson -- Corporate governance: Operating as an open book / Ted McDougal, Kurt P. Stocker -- Career paths in public relations / Jean Cardwell, Dana Rubin -- The chief executive officer: The key spokesperson / John D. Graham -- Crisis communications : Brand new channels, same old static / Hud Englehart -- Current and continuing issues in public relations: Sustainability for business: A new global challenge / Charlene Lake, Tony Calandro -- Environmental communication: a matter of relationship, trust and planning / Susan Croce Kelly -- Relationship transformation: Shifting media boundaries / Kevin Clark -- Reputation management: Building and maintaining reputation through communications / Craig E. Carroll, Stephen A. Greyser, Elliot S. Schreiber -- Industries and organizations: The automotive industry: A race to the future / Ray Day, Stephen J. Harris -- The aviation industry and civil aviation: Flying high for business / Robert P. Mark -- The insurance industry: Reputation management in good hands / Robert P. Gorman, James M. Dudas -- The hospitality industry: Communicating with our guests / John Wallis -- Sports marketing: Champion communicators / Amy D. Littleton,Steven H. Lesnik -- Effective technology communications : Innovation that matters / Edward Barbini, Rob Flaherty -- The entertainment business : Lights, cameras, promotion / Rob Doughty -- Healthcare: Harmonizing the health care message / Richard T. Cole -- The global restaurant industry: Communication strategies / Jonathan Blum --The retail industry: Not your father's drugstore / Michael Polzin -- The pharmaceutical industry: From promotion to constituency relations / Elliott S. Schreiber -- Consulting, technology services and outsourcing: An integrated approach to marketing and communications / Roxanne Taylor, Jayme Silverstone -- The financial and banking industry: Investing in our stakeholders / Anonymous -- The food and beverage industry: Catering to people's palates / Richard L. Nelson, Marguerite Copel -- The oil and natural gas industry: Communicating in a challenging environment / Sam Falcona -- Internal and external communications in a law firm / Mark Bain--Practical skills and knowledge: Changing your own behavior to enhance behavioral results / Kerry D Tucker, Bill Trumpfheller -- Creativity: Powering integrated marketing communications ideas / Marty Kohr -- Writing for the ear: The challenge of effective speechwriting / Lee W.Huebner -- Writing for your audience matters more than ever / George Harmon -- Storytelling: All stories are true / Emma Caywood -- Branded content strategy: Meaningful stakeholder interaction / Sara E. Smith, Clarke L. Caywood -- Immersive 3-D virtual worlds: Avatars at work / Anders Gronstedt -- Global public relations networks: The efficacy and role of membership organizations in public relations / Gerard F. Corbett -- Conclusion: The future of public relations and integrated marketing communications / Clarke L. Caywood.
Rev. ed. of: The handbook of strategic public relations & integrated communications. c1997.
Includes bibliographical references and index.
Keywords: Public relations; Communication in management; Communication in marketing